The Role of Non-Governmental Organizations in Preventive and Protective Education for Persons with Disabilities Experiencing Sexual Violence - Alya Nuraini; Hadiyanto Abdul Rachim; Gigin Ginanjar Kamil Basar (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study explores the role of Non-Governmental Organizations (NGOs) in providing preventive and protective education for persons with disabilities who have experienced sexual violence, viewed through a social work perspective. The research conducts a qualitative literature review which analyzes academic articles and institutional reports along with relevant publications that cover disability and sexual violence and social protection matters. The findings show that sexual violence against persons with disabilities cannot be seen solely as an individual issue, but rather as a consequence of structural inequality, social stigma, limited access to services, and weak institutional responses. In this context, NGOs play an important educational role by promoting public awareness, legal advocacy, psychosocial support, preventive education, and collaboration with other institutions. From a social work perspective, non-governmental organizations function as both service providers and advocates for developing more inclusive protection systems that respond to human needs. Strengthening collaboration and institutional capacity is therefore essential to ensure sustainable and rights-based protection for persons with disabilities.